Human Serum Albumin Nanoparticles: Synthesis, Optimization and Immobilization with Antituberculosis Drugs - Galiyeva, A.; Daribay, A.; Zhumagaliyeva, T.; Zhaparova, L.; Sadyrbekov, D.; Tazhbayev, Ye.T. (Polymers, 2023)
The aim of this study was to create nanoparticles of human serum albumin immobilized with anti-TB drugs (rifampicin, isoniazid) using the desolvation method. Central Composite Design (CCD) was applied to study the effect of albumin, urea, L-cysteine, rifampicin and isoniazid concentration on particle size, polydispersity and loading degree of the drugs. The optimized nanoparticles were spherical in shape with an average particle size of 216.7 3.7 nm and polydispersity of 0.286 4.9. The loading degree of rifampicin and isoniazid in the optimized nanoparticles were 44% and 27%, respectively. The obtained nanoparticles were examined by Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC); the results showed the absence of drug–polymer interactions. The drug release from the polymer matrix was studied using dialysis membranes.
Keywords: nanoparticles; albumin; rifampicin; isoniazid; antituberculosis drugs; desolvation